Media Visual Sebagai Strategi Pembelajaran Inklusif Bagi Anak Berkebutuhan Khusus di Sekolah Alam Depok - Reni Novia; Radyta Achmad Burhanuddin; Tri Suharman; Mahdalena Lubis; Frisyia Audrey Lynn Assegaf; Hesti Pratama Andani; Fika Rahayu (Universitas Islam Syekh Yusuf, 2026)
Inclusive education requires learning strategies that accommodate the diverse needs of all students, including children with special needs. One effective approach is the use of visual media in the teaching and learning process. This study aims to examine the role of visual media as an inclusive learning strategy for children with special needs at Sekolah Alam Depok. The research employs a qualitative approach using a case study method. Data were collected through classroom observations, in-depth interviews with teachers and learning assistants, and documentation of learning activities. The findings reveal that visual media, such as pictures, flashcards, educational videos, infographics, and visual teaching aids, significantly enhance students’ attention, comprehension, and active participation in classroom activities. The use of visual media also assists teachers in delivering learning materials more concretely, reducing communication barriers, and creating a more inclusive and supportive learning environment for students with diverse educational needs. Furthermore, visual-based learning supports the development of students’ cognitive, social, and emotional skills by fostering more effective interactions between teachers and learners. The study concludes that visual media plays a strategic role in supporting the success of inclusive education at Sekolah Alam Depok. Therefore, the development and utilization of creative, adaptive, and learner-centered visual media should be continuously enhanced to promote effective, meaningful, and equitable learning experiences for all students.